1989
DOI: 10.1016/0163-7258(89)90097-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of phosphonoformate (pfa, foscarnet sodium)

Abstract: This article describes the antiviral properties of foscarnet (trisodium phosphonoformate) at the enzyme level as well as in cell cultures and in vivo. The mechanism of action against herpesvirus DNA polymerases and reverse transcriptases is outlined. Clinical studies using topical foscarnet against mucocutaneous herpes simplex virus infections are presented. The clinical use of intravenous foscarnet against severe viral infections caused by cytomegalovirus, hepatitis B virus and human immunodeficiency virus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(42 citation statements)
references
References 167 publications
0
42
0
Order By: Relevance
“…Although the inhibition of viral DNA polymerases by PFA has been described many years ago (14,26,27), the detailed mechanism of action of this compound remains elusive (1,28). Previous biochemical studies about the mechanism of action of PFA focused on the inhibition of DNA polymerization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the inhibition of viral DNA polymerases by PFA has been described many years ago (14,26,27), the detailed mechanism of action of this compound remains elusive (1,28). Previous biochemical studies about the mechanism of action of PFA focused on the inhibition of DNA polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been consistently found that PFA competitively inhibited the ATP-PP i exchange reaction (26,29), and PFA has been used as a pyrophosphate analog for product inhibition studies in a variety of DNA polymerases (29,30). The interaction between foscarnet and pyrophosphate is not completely straightforward, however, because high levels of resistance to foscarnet are usually not associated with high levels of resistance to PP i (14,26,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrophosphate analog foscarnet (phosphonoformic acid, PFA) is the third approved anti-HCMV drug that inhibits UL54 ( Fig. 1) (28,29). However, toxicity, problems with oral bioavailability, and the rapid development of resistance can limit the clinical utility of each of the approved drugs.…”
mentioning
confidence: 99%
“…PFA is a broad spectrum antiviral agent that was shown to inhibit various polymerases, including enzymes encoded by herpes simplex virus (HSV), human herpesvirus, HCMV, and the reverse transcriptase (RT) of the human immunodeficiency virus type 1 (HIV-1) (28,29). Progress has been made in elucidating the mechanism of inhibition of HIV-1 RT (30,31).…”
mentioning
confidence: 99%